2018
DOI: 10.1007/s12664-018-0868-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute intractable vomiting: Do I belong somewhere else?

Abstract: Patients suffering from acute intractable vomiting are usually treated in the Gastroenterology department. The causes of acute intractable vomiting range from acute pancreatitis and acute intestinal obstruction to cardiac causes like acute myocardial infarction and neurological causes like posterior circulation stroke. However, most of the underlying causes of acute intractable vomiting also produce other telltale signs/symptoms. Rarely, isolated acute intractable vomiting may be the initial symptom of a recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This is consistent with the past cases reported in the literature [8,12]. Despite many cases being reported from the region of Asia, particularly many from India [11], the case in hand is the solitary case of NMO presenting with intractable vomiting to be reported from Pakistan and can be considered a stepping-stone for this under-reported subject.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the past cases reported in the literature [8,12]. Despite many cases being reported from the region of Asia, particularly many from India [11], the case in hand is the solitary case of NMO presenting with intractable vomiting to be reported from Pakistan and can be considered a stepping-stone for this under-reported subject.…”
Section: Discussionsupporting
confidence: 90%
“…Jin X et al reported 12 cases of NMO with a similar presentation, of which 83% were aquaporin-4 antibody positive [9], while another study reported 14 cases of NMO with similar initial manifestations as well [10]. More reports can be found in the literature from Asia, including cases from India and China [11,12]. Contrary to our case, intractable hiccups were also a prominent symptom of NMO in other cases [13].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation